Anisotropic α‐Fe2O3@TiO2 Core–Shell Nanoparticles and Their Smart Electrorheological Response. Issue 3 (23rd December 2014) - Tian, Xiaoli; Yin, Yichao; Wang, Baoxiang; Song, Xianfen; Sun, Shuangshuang; Yu, Shoushan; Hao, Chuncheng; Chen, Kezheng
Abstract: α‐Fe2 O3 @TiO2 core–shell nanoparticles were prepared through a combination of reflux and hydrolysis methods. Firstly, a spindle‐like and monodispersed α‐Fe2 O3 nanorod core was fabricated by using a reflux method. In the second step, an amorphous TiO2 shell was coated onto the surface of the nonspherical α‐Fe2 O3 core with a uniform thickness by means of a controlled hydrolysis method. The morphology, structure, and electrorheological (ER) activity of α‐Fe2 O3 @TiO2 core–shell nanoparticles were determined by X‐ray powder diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), magnetic testing, and by using a rotational rheometer. The resulting nonspherical core–shell nanoparticles possess the advantages of uniform sizes, weak magnetism, and smart electrorheological behavior. An enhanced ER effect is found with the α‐Fe2 O3 @TiO2 and hollow TiO2 ER suspension compared with that of a pure α‐Fe2 O3 ER suspension. Abstract : α‐Fe2 O3 @TiO2 core–shell nanoparticles were synthesized by means of a controlled hydrolysis method and can be used as smart electrorheological (ER) materials. The nonspherical core–shell nanoparticles possess uniform sizes and weak magnetism. The α‐Fe2 O3 @TiO2 ER suspension exhibits an enhanced electrorheological effect compared with that of a pure α‐Fe2 O3 ER suspension.